2022
DOI: 10.5964/jspp.7477
|View full text |Cite
|
Sign up to set email alerts
|

Child’s presence shapes immigrant women’s experiences of everyday intergroup contact

Abstract: Research on intergroup contact has considered how the occurrence and experience of contact is affected by ingroup members. Qualitative studies of contact in real-life settings have additionally highlighted how multiple actors can affect the manifestation of contact. This article shows how the presence of one’s child can shape immigrant mothers’ contact experiences in multi-ethnic neighbourhoods. Ten immigrant mothers living in Helsinki, Finland, were interviewed twice over a six-month period about their interg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Being a mother often leads to changes in social relationships of a woman and increases the need for peer support and, therefore, this stage of life could also afford opportunities for intergroup contact among mothers in ethnically diverse neighbourhoods. When conducting an ethnography as a part of this project, however, we observed that intergroup contact among mothers was rare or described as improbable, and that in the absence of these peer contacts less optimal types of everyday contact became meaningful to many mothers with immigrant background (Paajanen et al, 2022, 2023; Riikonen et al, 2023). In the interviews, which we started at the same with ethnography, we aimed to investigate the everyday life and contacts by asking the respondents about their social relations (e.g., ‘Describe the friendships and relationships you have currently/you have had since the last interview’), everyday life in the neighbourhood (e.g., ‘How the ways and places of spending time have changed when your baby has grown?’), motherhood (e.g., ‘Where and how do you spend time with your child(ren) in the neighborhood?’), and diversity (e.g., ‘Have you got to know mothers from other cultures?’), but not specifically about their encounters with kindergarten and playground workers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being a mother often leads to changes in social relationships of a woman and increases the need for peer support and, therefore, this stage of life could also afford opportunities for intergroup contact among mothers in ethnically diverse neighbourhoods. When conducting an ethnography as a part of this project, however, we observed that intergroup contact among mothers was rare or described as improbable, and that in the absence of these peer contacts less optimal types of everyday contact became meaningful to many mothers with immigrant background (Paajanen et al, 2022, 2023; Riikonen et al, 2023). In the interviews, which we started at the same with ethnography, we aimed to investigate the everyday life and contacts by asking the respondents about their social relations (e.g., ‘Describe the friendships and relationships you have currently/you have had since the last interview’), everyday life in the neighbourhood (e.g., ‘How the ways and places of spending time have changed when your baby has grown?’), motherhood (e.g., ‘Where and how do you spend time with your child(ren) in the neighborhood?’), and diversity (e.g., ‘Have you got to know mothers from other cultures?’), but not specifically about their encounters with kindergarten and playground workers.…”
Section: Methodsmentioning
confidence: 99%
“…Although this has shown intergroup contact to be effective (Pettigrew & Tropp, 2006), several authors have criticized traditional contact research for its distance from real‐life contacts that are embedded in their material and socio‐historical context (Dixon et al, 2005; McKeown & Dixon, 2017). Critical contact research has approached the problem by studying everyday intergroup contact in places where people actually spend time, showing that contact is often scarce, superficial, or even avoided (Alexander & Tredoux, 2010; Dixon & Durrheim, 2003; Paajanen, Seppälä, Stevenson, & Finell, 2022; Paajanen, Seppälä, Stevenson, Riikonen, & Finell, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A diverse neighborhood can provide a number of opportunities for inter- and intraethnic encounters for the parents of young children (e.g., Paajanen et al forthcoming; Schaeffer 2013; Wilson 2013). Such encounters can help immigrant mothers create positive relationships with majority group mothers, thus benefiting the integration of immigrant mothers and enhancing the social cohesion of the community (see Stevenson and Sagherian-Dickey 2016).…”
Section: Context Of the Study: Public Playgrounds In Helsinki Finlandmentioning
confidence: 99%
“…In Helsinki, intergroup contacts and friendships between Finnish majority mothers and immigrant mothers are quite rare (Paajanen, Seppälä, Stevenson, & Finell, 2022 ; Paajanen, Seppälä, Stevenson, Riikonen, & Finell, 2022 ). One way to better understand this phenomenon is to investigate whose actions are constructed as leading to contact or its avoidance.…”
Section: Introductionmentioning
confidence: 99%